Analysis of interactive media integrated natural science with energy themes in the life of using integrated types that integrate of learning for the 21st century. (March 2020) - Ariani, Rizka; Ratnawulan,
Abstract: 21st Century Learning is learning that integrates literacy skills, knowledge skills, skills and attitudes, and mastery of ICT technology. Teacher professional competency demands on 21st Century learning must have the skills to be a model of how to learn and work by demonstrating proficiency in technology and transferring knowledge to technology, and collaborating with students and colleagues in using various relevant tools and resources to drive the success of technological mastery innovation. To face the challenges of the 21st Century, Integrated Science interactive media should be able to describe the skills expected in 21st Century learning. The preliminary study carried out aims to analyze the basis in the design of interactive science media integrated with the theme of energy in integrated type life of integrated learning in the 21st century. Research will be conducted using descriptive type research and qualitative approaches. In this study the researchers chose a sample of students at SMPN 11 Padang. Data through questionnaires and interview sheets are primary data that will be used in this research. The results of the analysis state that learning media are needed to help students possess critical thinking skills integrated in 21st century learning.